2018
DOI: 10.1186/s12877-017-0683-1
|View full text |Cite
|
Sign up to set email alerts
|

What works in falls prevention in Asia: a systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundThere is strong research evidence for falls prevention among older people in the community setting, although most is from Western countries. Differences between countries (eg sunlight exposure, diet, environment, exercise preferences) may influence the success of implementing falls prevention approaches in Asian countries that have been shown to be effective elsewhere in the world. The aim of this review is to evaluate the scope and effectiveness of falls prevention randomized controlled trials (RCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 61 publications
2
55
0
3
Order By: Relevance
“…For example, in the inpatient setting, a study by Vassallo et al found that the hospital wards with more inpatient beds within the sightline of the nursing station had fewer falls than the ward with poor visibility between beds and the nursing station 39. Location-specific research in falls prevention has also shown that exercise, home modification, educational materials and vision correction are all important 40 41. It is also important to consider how morbidity or mortality resulting from falls might be mitigated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the inpatient setting, a study by Vassallo et al found that the hospital wards with more inpatient beds within the sightline of the nursing station had fewer falls than the ward with poor visibility between beds and the nursing station 39. Location-specific research in falls prevention has also shown that exercise, home modification, educational materials and vision correction are all important 40 41. It is also important to consider how morbidity or mortality resulting from falls might be mitigated.…”
Section: Discussionmentioning
confidence: 99%
“…Through the systematic search, we identified 115 records, including two review articles (Hill et al, 2018;Puts et al, 2017). An additional review article was identified by a manual search .…”
Section: Study Selectionmentioning
confidence: 99%
“…Segundo Hill et al (2018) ao realizar uma revisão sistemática para verificar o que funciona na prevenção de quedas para idosos na Ásia, a prática constante de atividades físicas sistematizadas foi a que mais obteve resultados significativos, tanto no número quanto nas lesões acometidas pelas quedas.…”
Section: Introductionunclassified